A study of geo-polymer as alternative material in automotive brake pad - Z., Embong; S., Shahudin; S., Hassan; M. S., Yusof; S., Mahzan; S., Shamsuddin; N. K., Othman; M. A. A., Mohd Salleh (2021)
Todays, there are various of alternative materials that have been studied by many researchers in order to find the appropriate combination of brake pad manufacturing in the automotive industry. Some of the alternative materials that has being used including palm slag, banana peels, nutshell and others. This provide more economical benefit and also environmental preservation by utilizing the waste of natural fiber. In this study, geo-polymer brake pad has been prepare using the waste product which is barren soil. Barren soil is chosen as an alternative brake pad material candidate from natural resources as it consists of deserts, dry salt flats, beaches, sand dunes, exposed rock, strip mines, quaries, and gravel pits. This barren soil are mixed with another candidates such as binder, reinforcement, abrasives and lubricant following the standard formulation of brake pad manufacturing. In this works, three type of samples have been used. The elemental composition for sample 1, 2 and 3 are main content with 10%, 5%, 15% alumina and 10%, 15%, 5% graphite respectively. The physical properties of geo-polymer brake pads studied including hardness test and its morphology structure. Sample has been characterized based on two main parameters which are hardness test and morphology analysis. From the analysis, it was found that a prototype from sample 3 exhibit the highest hardness index compare to sample 1 and 2. Sample 3 hardness also much better compare to the conventional brake pad with 64% of the hardness increment. This finding also support by the morphological analysis, whereby the surface of sample 3 show a compact and flat surface with less cracking and porosity. From both parameter, it can be concluded that sample 3 has a great potential to become a suitable geo-polymer brake pad. Here, the composition of a combination alumina and graphite in all sample play as important role in enhance the hardness parameter for the potential brake pad prototype.